VELARDE HOUSE. FROM METHOD TO MATERIALITY - ALBORNOZ-RODRÍGUEZ, Heberto (2024)
The design method is in no way separated from the constructive vision. Aristotle perceived the world as the here-and-now of the idea, which, in its hylomorphism was embodied in matter. The theory of the four causes certifies this. Every event comes from movement, the efficient cause in architecture is necessity; the purpose is to inhabit; the formal cause is the way of thinking and the material cause is the constructive system that supports it. The useful technique is the way of creating architecture in antiquity, and it meant at the same time a knowing-how to think and knowing-how to do, this is what this article discusses about the methods that produce materiality, applied to the Velarde house as an incarnation of Peruvian modernity.